Bimodal soil pore structure investigated by a combined soil water retention curve and X-ray Computed Tomography approach - Zhou, Hu; Mooney, Sacha J.; Peng, Xinhua (Soil Science Society of America, 2017)
Well-structured soils are generally considered to have bimodal pore structure, including textural pores between soil particles and structural pores between soil aggregates. Bimodal pore structure has previously been inferred indirectly from the soil water retention curve (SWRC) but our understanding of the precise 3-D pore geometry that regulates this curve is limited. The objective of this study was to investigate the bimodal pore structure of a paddy soil under different fertilization regimes using both SWRC and X-ray micro-Computed Tomography (micro-CT), an imaging approach with the aim of comparing the two methods. Undisturbed soil aggregates and soil cores were collected from the surface layer of a long-term unfertilized control (CK), inorganically fertilized (NPK), and organically and inorganically fertilized (NPKOM) paddy soils. The aggregates and cores were scanned using micro-CT and pore structure analyzed. The SWRCs were measured on the same CT-scanned soil cores. Three widely used unimodal models, three bimodal models, and one trimodal model were evaluated for their fit to the SWRC and to derive soil pore size distribution (PSD). Results showed the SWRC of the paddy soil were best fitted with the bimodal lognormal (BLN) and double-exponential (DE) models, with the derived PSD showing distinct bimodality. The micro-CT images revealed the hierarchy structure of the paddy soil and a distinct bimodal pattern in the PSDs. The structural porosities from BLN, DE models and from CT imaging are consistent, and all correlated with the natural logarithm of saturated hydraulic conductivity. Long-term application of NPKOM increased structural porosity though no changes were recorded in the textural porosity compared with NPK and CK treatment, while the latter two showed a near identical pore structure. The results of this study showed the consistence of the SWRC and imaging method in studying soil pore structure and supported the use of bimodal SWRC models to investigate the pore structure of the well-structured paddy soil.